Lideranças Krikati: implicações da escola não indígena em suas trajetórias e trajetórias de vida - Silva, Ilma Maria de Oliveira (Universidade do Vale do Rio dos Sinos, 2018)
This thesis examines the story and life journeys of two Krikati leaders, taking into consideration the implications of non-indigenous school in their education. The research is conducted by understanding that social, political, cultural, economic and linguistic organization of each indigenous people is dynamic and, therefore, the appropriation of knowledge and values of other cultures comes from human relations and the history of contact itself. In the sense, we defend that in the processo f formation of indigenous schools contributed in their trajectories and life histories without dissolving their culture and indigenous identity. The research pointed out that the sociocultural differences in schools are configured as fundamental elements for the social relations and as a path that opens up for the construction of an intercultural curriculum, even though the difficulty of it to be recognized and institutionalized within the pedagogical practices of schools still prevails. It has been sought out to understanding the social and political context - 1980 to 1990 - in which, for the first time in Brazilian history, the right to education for indigenous peoples is constitutionally guaranteed, strengthening the socio-cultural practices, respect for their native languages and their own learning processes. The research was developed considering the life stories of Silvia Cristina Puxcwyj Krikati and Lourenço Borges Milhomem Acỳxit Krikati and, particularly, from their journeys in non-indigenous schools in the west region of the state of Maranhão. The determination of these for appropriating western knowledge has contributed to the strengthening of their leadership skills and, consequently, to the implementation of projects in the Indigenous Territory Krikati, especially in relation to education, health, the environment and, above all, in the participation in indigenous movements and organizations. Thus, we embrace in this study the theoretical-methodological basis of the history of the present time and history with oral sources. At the present time we had the opportunity to examine the peculiarities of each subject as living witnesses of their own life stories. As for the methodology of oral history, we do not concern with absolute truths, but with the experiences lived by the sources, as well as by the interlocutors themselves. Therefore, the survey revealed that regardless of where you are geographically located and the curriculum that the schools offer, they have contributed to the formation of krikati leaders, because it resulted in the acquisition of mastery of structuring basic codes of non-indigenous society, specially, the one of Portuguese language, as well as the useful and necessary knowledge for the improvement of life conditions both individually and within their communities.
Keywords: Lideranças indígenas; Krikati; Trajetórias; Escola não indígena; Indigenous leaderships; Krikati; Trajectories; Non-indigenous school; ACCNPQ::Ciências Humanas::História